O Programa Cooperação na Ponta do Lápis e seu propósito em cooperar para uma vida financeira sustentável - Ostemberg, Eber Silva (2022)
It is a fact that Financial Education is an urgent issue in contemporary society as well as it is a fact that its dissemination is not yet at an ideal level. The theme has been slowly worked on by the state and private organizations for more than a decade and its results are still small in the face of the great challenges and social problems caused by the capitalist system that organizes and dictates the progress of our society. This research analyzed the Financial Education Sicredi’s program “Cooperação na Ponta do Lápis” created in 2020 and had as its General Objective, verify the fulfillment of its purpose which is to "Cooperate for a Sustainable Financial Life" and as Specific Objectives, describe the historical process of the Program and its theoretical framework. The research-action research was carried out with 10 participants between 18 and 34 years old residing in the city of Rio Branco - AC and had a qualitative methodological approach based on the epistemological conception of historical-dialectical Materialism proposed by Marx and theoretical contributions by George Simmel, Paulo Freire, among others. Two face-to-face meetings were held with the participants, semi-structured interviews before and after the completion of the training with the application of the methodology proposed by the Program “Cooperação na Ponta do Lápis” and had as two methods of analysis being the Analysis by Core of Meaning according to Aguiar and Ozella (2013) and Comparative Qualitative Analysis along the lines of Schneider and Schmitt (1998). From the proposed analyzes and results of the methods, the research arrived at the positive result that the Cooperação na Ponta do Lápis fulfills its purpose of “Cooperating for a sustainable financial life”, raising awareness of the importance of Financial Education and its practices, increasing the perception of how expenses influence the subjects' quality of life, awakening to the importance of budgeting and planning for the realization of dreams, as well as reducing expenses, especially regarding variables and superfluous and the increase in the act of saving. As a result, the participants also acquired an understanding of the role of cooperativism and Sicredi in improving the quality of life of people and communities, and contributions to the improvement of the program were also listed.